(untitled) (Research, Society and Development, 2022)
Transmissible venereal tumor (TVT) is a round cell cancer that predominantly affects the external mucosa in dogs however; the occurrence of metastases is unusual. The aim of this study was to report the clinical, cytopathological, histopathological and immunohistochemical findings of a case of cutaneous and splenic TVT without the presence of genital lesion in a 4-year-old mongrel bitch was treated at the Veterinary Hospital of the Federal University of Uberlandia. A clinical examination revealed subcutaneous nodules caudal to the knee, scapular region, and left inguinal and third thoracic vertebra. Aspiration of all the nodes was performed using fine needles. In ultrasound examination of the abdominal region, an enlarged spleen was observed. Splenectomy was performed in the animal, and a macroscopic examination showed a nodule approximately 15 cm in diameter. Fragments of the mass were sent to the histopathology laboratory of the Veterinary Hospital of the Federal University of Uberlandia where they were processed routinely. Due to the unusual location of the tumor in the spleen, where lymphoma and histiocytoma are more frequent, and because TVT, histiocytoma, and lymphoma are round cells, an immunohistochemical examination was performed for a differential diagnosis. The multifocal cutaneous and splenic location is rare, as well as the metastatic behavior of the transmissible venereal tumor and in these cases the immunohistochemical confirmation is advisable.